Anatomical and Functional Results Following 23-Gauge Primary Pars Plana Vitrectomy for Rhegmatogenous Retinal Detachment: Superior versus Inferior Breaks - Panagiotis Stavrakas; Paris Tranos; Angeliki Androu; Paraskevi Xanthopoulou; Dimitrios Tsoukanas; Polixeni Stamatiou; Panagiotis Theodossiadis (Journal of Ophthalmology)
Purpose. In this retrospective study, we evaluated the anatomical and functional outcomes of patients with rhegmatogenous retinal detachment primarily treated with pars plana vitrectomy in regard to the location of the breaks. Methods. 160 eyes were enrolled in this study, divided into two groups based on break location: the superior break group (115 eyes) and the inferior break group (45 eyes). The main endpoint of our study was the anatomical success at 3 months following surgery. Results. Primary retinal reattachment was achieved in 96.5% of patients in group A and in 93.3% in group B (no statistically significant difference, OR 1.98, 95% CI: 0.4, 7.7). Mean BCVA change and intraoperative complication rate were also not statistically significantly different between the two groups (p>0.05, OR: 1.0, 95% CI: 0.9, 1.01, resp.). Statistical analyses showed that macula status, age, and preoperative BCVA had a significant effect on mean BCVA change (p=0.0001, p=0.005, and p=0.001, resp.). Conclusion. This study supports that acceptable reattachment rates can be achieved using PPV for uncomplicated RRD irrespective of the breaks location and inferior breaks do not constitute an independent risk factor for worse anatomical or functional outcome.